Membangun Profesionalisme Guru Pendidikan Agama Kristen di Era Digital - Norianti Pai Tiba; Santi Aplunggi; Jidro Alfindo Sabuin; Leni Kristiana Wabang; Serni Marwina Almet; Sarci Henukh; Viatni Yakoba Manu; Risto Umbu Lowu Pangerang; Aprilia Mengga (Educational Journal, 2026)
In the digital era, the professionalism of Christian Religious Education (CRE) teachers is a key element in enhancing the quality of faith-based learning and the spiritual character of students. This research aims to analyze strategies to strengthen the professionalism of CRE teachers in facing the transformation of digital education, while emphasizing the importance of digital ethics and spiritual guidance. The method used is library research, with comparative analysis of relevant reputable academic literature. The results show that CRE teachers need to adapt to technological advancements and enhance digital literacy to create interactive and engaging learning experiences. Difficulties in technology implementation by teachers are often caused by a lack of digital pedagogical skills. Therefore, training in digital literacy and collaboration between schools, families, and churches is highly recommended to build comprehensive teacher professionalism. This research concludes that improving the professionalism of CRE teachers can strengthen students' spiritual character, preparing them to face the challenges of the digital world with strong faith integrity.